First record of damage Leucothrips piercei (Thysanoptera: Thripidae) in pepper crops (Capsicum annuum L. (Solanaceae) in Argentina - Zamar, María Inés; de Borbón, Carlos Manuel; Aguirre, Alcides; Miño, Valeria; Cáceres, Sara (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
Leucothrips piercei (Morgan) is newly recorded from Argentina and Capsicum annuum L. is registered as a new host plant. The diagnostic characters are described and the characteristics of the damage to the leaves of pepper are provided.